Sistem Pendukung Keputusan Perbaikan Jalan menggunakan Metode Fuzzy Multi Atribute Decision Making (FMADM) dan Simple Additive Weighting (SAW) (Studi Kasus : Dinas Pekerjaan Umum Bina Marga dan Sumber Daya Air Kabupaten Jember) - Guntur Syafiqi Adidarmawan; Muhammad Tanzil Furqon; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Road repairs have been planned by Dinas Pekerjaan Umum Bina Marga dan SDA Kabupaten Jember by repairing 50 roads in the Jember City area. This road repair is carried out to increase the quality of roads with good condition to 70 percent from 61.88 percent. In the process of determining which roads will be repaired, there are difficulties encountered. There are many factors that need to be considered, so that it requires accuracy in decision making. This study aims to implement the FMADM and SAW methods in a decision support system to determine the priority ranking of roads that need improvement. In addition to implementing the algorithm and knowing its accuracy, this study also aims to determine how sensitive the criteria are. Based on research results, the accuracy results were 88 percent in the first scenario and 60 percent in the second scenario, and get a coefficient value of 0.470 on the Spearman Rank Correlation test. The results of the sensitivity test using 9 criteria were 92.11 percent. From the test, the criteria for moderate road conditions are the criteria that have the highest sensitivity by producing 99 ranking changes and the criteria for lightly damaged road conditions are the criteria with the lowest sensitivity with 72 ranking changes.